Struktur Komunitas Kupu-kupu (Lepidoptera: Papilionoidea) dan Floral Preferences di Kawasan Tancak Tulis serta pemanfaatannya sebagai Buku Ilmiah Populer - Balgis Salsabilah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Tancak Tulis is a waterfall tourist destination located on the western slope of Mount Argopuro. This area is a production forest zone and is classified as a protected forest. Butterflies (Lepidoptera: Papilionoidea) are among the insects found in this area. Observations of butterfly community structure and flower preferences aim to understand species composition, particularly in the Tancak Tulis area, which has not been extensively studied to date. This research was conducted from July 2025 to March 2026. Sampling locations were determined using purposive sampling in two habitat types: rubber plantations and coffee plantations. The sampling technique used was road sampling. Community structure analysis included the Shannon-Wiener diversity index, richness index, evenness index, dominance index, and similarity index. Species identification was based on relevant literature. A total of 20 species were identified from four families: Ypthima horsfieldii, Ypthima nigricans, Euploea mulciber, Euploea tulliolus, Melanitis leda, Mycalesis horsfieldii, Neptis hylas, Hypolimnas bolina, Eurema hecabe, Leptosia nina, Delias hyparete, Pareronia valeria, Appias lyncida, Appias olferna, Catopsilia pomona, Papilio memnon, Papilio polytes, Troides helena, Graphium sarpedon, and Nacaduba kurava. The most dominant species were Eurema hecabe and Ypthima nigricans. The community structure index (H’) with a value of 2.34 was categorized as moderate; (R), with a value of 2.34, is categorized as moderate; (E), with a value of 0.57, is categorized as high; (D), with a value of 0.13, is categorized as low; (SI), with a value of 78.79%, is categorized as high; (Rdi) indicates moderate abundance, with the species Eurema hecabe having the highest abundance. Most butterflies visit purple, yellow, and blue flowers with tubular shapes. The average validation score for this book is 88.6, categorized as very good.
Finalisasi 23 Juli 2026 Rudi H
Keywords: Abudance; Coffee plantations; Lepidoptera deversity; Rubber plantasions